Decreased Kidney Function Among Agricultural Workers In El Salvador - Peraza, Sandra (2012)
Background: An epidemic of chronic kidney disease of unknown cause has emerged along the Pacific coast of Central America, particularly in relatively young male sugarcane workers. In El Salvador, we examined residence and occupations at different altitudes as surrogate risk factors for heat stress. Study Design: Cross-sectional population-based survey. Setting & Participants: Populations aged 20-60 years of 5 communities in El Salvador, 256 men and 408 women (participation, 73%): 2 coastal communities with current sugarcane and past cotton production and 3 communities above 500 m with sugarcane, coffee, and service-oriented economies. Predictor: Participant sex, age, residence, occupation, agricultural history by crop and altitude, and traditional risk factors for CKD. Outcomes: Serum creatinine (SCr) level greater than the normal laboratory range for sex, estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2, and proteinuria categorized as low (protein excretion <30-<300 mg/dL) and high grade (<300 mg/dL). Results: Of the men in the coastal communities, 30% had elevated SCr levels and 18% had eGFR <60 mL/min/1.73 m 2 compared with 4% and 1%, respectively, in the communities above 500 m. For agricultural workers, prevalences of elevated SCr levels and eGFR <60 mL/min/1.73 m 2 were highest for coastal sugarcane and cotton plantation workers, but were not increased in sugarcane workers at 500 m or subsistence farmers. Women followed a weaker but similar pattern. Proteinuria was infrequent, of low grade, and not different among communities, occupations, or sexes. The adjusted ORs of decreased kidney function for 10-year increments of coastal sugarcane or cotton plantation work were 3.1 (95% CI, 2.0-5.0) in men and 2.3 (95% CI, 1.4-3.7) in women. Limitations: The cross-sectional nature of the study limits etiologic interpretations. Conclusion: Agricultural work on lowland sugarcane and cotton plantations was associated with decreased kidney function in men and women, possibly related to strenuous work in hot environments with repeated volume depletion.